2006
DOI: 10.1177/0003319706295518
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Balloon Aortic Valvuloplasty: A New Look at an Old Procedure

Abstract: There has been little change in the technical approach to balloon aortic valvuloplasty (BAV) over the last two decades. Large-caliber sheaths and extra-stiff wires have been used routinely to accommodate the large balloons used for this purpose. Consequently the morbidity (and possibly mortality) rates have been high. With the recent advances in the interventional hardware, a new look at the current approach to BAV is justified. In this report we describe an 89-year-old woman with critical aortic stenosis who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Recent data on BAV suggest that technical and procedural advances have decreased procedural complication rates in high‐risk patients, suggesting that increased utilization of the procedure is warranted in the growing subset of patients with limited therapeutic options [8–11]. As such, BAV is currently used as a palliative procedure for high‐risk patients who are precluded from surgical AVR or as a bridge to surgery in hemodynamically unstable patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…Recent data on BAV suggest that technical and procedural advances have decreased procedural complication rates in high‐risk patients, suggesting that increased utilization of the procedure is warranted in the growing subset of patients with limited therapeutic options [8–11]. As such, BAV is currently used as a palliative procedure for high‐risk patients who are precluded from surgical AVR or as a bridge to surgery in hemodynamically unstable patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…The only serious complication experienced in the current series of 20 patients during the first 24 hours after BAV was tamponade in 1 patient. In two previous large series of patients undergoing BAV, cardiac tamponade was reported in 3 of 170 consecutive patients (1.8%) 6 and 10 of 672 patients (1.5%) 3…”
Section: Resultsmentioning
confidence: 91%
“…A recently published case report suggested that using small profile peripheral balloons may reduce complications, with a patient successfully treated using an 8‐French (F) arterial sheath 6 . The current report describes a case series of consecutive patients with severe aortic stenosis referred for BAV and treated in routine clinical practice using a valvuloplasty technique developed by the first author and designed to optimize valve opening while also improving procedure safety.…”
Section: Introductionmentioning
confidence: 99%